EXPLOITATION DU CHARBON DE BOIS ET RISQUES SANITAIRES EN PAYS ODJUKRU - Siméon, Akmel Meless (European Scientific Journal, ESJ, 2012)
﻿The charcoal activity has become universal reaching Europe, Asia and Africa. Côte d’Ivoire, mainly a farming country is not left out in so far as farmers everywhere devote themselves to its production. The case of Aklodj, an odjukru village is an illustration of it. In fact, the qualitative research of ethnographic type through the representation of charcoal activity by local dealers shows that the production of charcoal has a double targets in this village, since it fulfils two main functions: it is manifest (economic and social) and latent (cultural) . However it indicates above all that the producers are aware of the diseases and the industrial accident this activity causes. In spite of this contradiction or uncomfortable situations, the dealers devote themselves to its production, what explains our concern and impose an approach likely to eradicate or failing that to minimize the problems of health.